The Application of International Financial Reporting Standards in the Dairy Horse Breeding in Supply Chain Management - G.A Khabirov; Z.Z Suleymanov; A.M Ableeva; G.A Salimova; E.I Galimova (International Journal of Supply Chain Management, 2019)
The article discusses the prospects for the introduction of the Russian accounting practice of International financial reporting standards (IFRS), the calculation of the fair value of the biological asset of horse breeding organizations under IFRS. A number of methods of calculation of fair value, a technique based on market value and calculation based on the method of profit capitalization and money flow discounting are considered to justify the effectiveness of supply chain management. To prove the necessity and effectiveness of the implementation of IFRS in the production calculations were made on the example of OJSC "Ufa horse breeding farm â„–119", the leading enterprise for the industrial production of medicinal mare's milk. When using the method based on market value, it is clear that the profit of the organization, when using the calculations of biological assets at fair value, is more by 4.4 million rubles, than reflected in the balance sheet. In the case of calculations based on the method of profit capitalization, the balance sheet increase by more than 7 million rubles. Calculations indicate that the carrying amount of biological assets is significantly understated in relation to the fair value. Distortion of real value indicators leads to a false assessment of the effectiveness of the use of assets in organizations producing agricultural products, as well as creates difficulties in making appropriate decisions in the management sphere. Accounting for biological assets of the organization at fair value will improve the reliability of the financial results of the agricultural organization and will help to assess the results of economic activity more accurately; it will contribute to the adoption of correct and timely management decisions on the choice of supply chain management strategy. It will significantly increase investment attractiveness of agricultural organizations and the whole industries.